Implementing Think-Pair-Share Strategy and Audio-Visual Media to Overcome Student Sleepiness During English Lessons at SMA Nurul Jadid - Cahyani, Intan; Mohammad Sofyan Adi Pranata; Mustaina (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this investigation was to tackle the problem of students feeling sleepy in English class at Nurul Jadid Senior High School by using a Think-Pair-Share (TPS) method along with audio-visual resources. The methodology utilized was Classroom Action Research, carried out across a pair of cycles, with each cycle encompassing planning, acting, observing, and reflecting. Thirty-two students from the eleventh grade took part in the study. The methods for gathering information involved observation forms, scales for rating sleepiness, conversations, and records. The findings demonstrated a noticeable lessening of student drowsiness. Initial information prior to the cycles showed that 59.4% of the students were sleepy, but this fell to 28.1% in the first cycle and then even further to just 9.4% in the second cycle. There was a significant rise in student involvement, with active participation jumping from 34.4% up to 84.4%. Using TPS alongside audio-visual tools is a fresh way to deal with sleepiness in the classroom by bringing together working as a group with stimulation for multiple senses.